The effect of green biobased binder on structural, mechanical, liquid absorption and wetting properties of coated papers - Altay B.N.; Klass C.; Chen T.; Fleck A.; Aydemir C.; Karademir, Arif; Fleming P.D. (Elsevier Ltd, 2021)
Synthetic styrene-butadiene (SB) and styrene-acrylic (SA) latex binders used in paper coating formulations are common and based on unsustainable petroleum sources. Today's papermaking industry turns towards sustainable substitutes that do not compromise quality, and reduce carbon emission, toxic substance release and waste disposal concerns related to fossil fuel sources. In this study, colloidal starch-based latex nanoparticles that do not require cooking were used for pigment coating and coated on the paper surfaces. The effects of these new biobased binders on the structural and mechanical strength properties, liquid absorption, wetting and surface topography of the paper were investigated and compared with the properties of coated paper that SB latex was used as a coating binder. The results demonstrated that the biobased latex decreases the grammage of paper while maintaining an identical thickness relative to the SB latex samples. The porosity, permeability and roughness of biobased latex are found higher than the SB latex. The biobased latex successfully replaced SB latex at 1:1 ratio and enabled an equivalent of bursting, tear, tensile strength and structural properties.
Keywords: Biomaterial; Coating; Mechanical properties; Starch; Structural properties